Human exposure to indoor air pollution in Ethiopian households - Elsai Mati Asefa; Mekuria Teshome Mergia (Heliyon, 2022)
Because most people spend the majority of their time in microenvironments, indoor air pollution (IAP) has gained more attention than outdoor air pollution recently. It is indeed crucial to understand IAP sources and the factors that influence human exposure. We synthesized evidence on IAP levels and contributing factors in Ethiopia from available literature, utilizing findings from 19 studies to retrieve 66 relevant values. Particulate matters (PM2.5, PM4, PM10, and TSP), as well as gaseous pollutants such as carbon monoxide (CO), nitrogen dioxide (NO2), polyaromatic hydrocarbons (PAHs), and total volatile organic compounds (TVOCs), were analyzed. The calculated mean concentrations for PM2.5, PM10, NO2, TVOCs, and CO were 477.47 μg/m3, 228.38 μg/m3, 63.84 μg/m3, 1361.79 μg/m3, and 18.82 ppm, respectively, all of which exceeded the annual WHO exposure guidelines. Geographical location, stove type, and household activities showed a variation in pollutants concentration. The higher levels of pollutants were attributed to emissions from biomass fuel used for baking injera, wot preparation, and conducting a coffee ceremony, as well as poor ventilation, season, cooking time, and tobacco smoke. The health risk assessments for exposure to various domestic activities were found to be acceptable, except for PM10, with the highest correlation with an acute respiratory infection. Although improved cookstove technology has been proposed as a sustainable energy source, investigations in Ethiopia have revealed that there is still room for public health protection. There is a paucity of research on the relationship between indoor and outdoor air pollution. Future research should prioritize these issues, with a focus on the link between IAP exposure and health effects. In conclusion, there is a higher IAP concentration in Ethiopia so the community should be made aware of it as well as related health effects, and immediate mitigation measures are needed to achieve a reduction in exposure.